Tradition as a Factor in Modern School Formation in Ukrainian Piano Pedagogy - Guralnyk, Nataliia; Xinyan, Ma (Journal of History Culture and Art Research, 2019)
The entry of Ukraine as an independent entity into the European educational space ensures the national identity of musical and educational phenomena, as well as actualizes the significance of the Ukrainian Piano School as a world heritage, determines the introduction of its pedagogical achievements to general scientific community. Our definition of piano school in Ukraine, as a national musical and educational phenomenon, is based on many dimensions. Actualization of scientific thought revealed the wide theoretical and educational possibilities of the Ukrainian piano school as a scientific-pedagogical and national-educational phenomenon. The methodological and theoretical concept of this study provided the integrated application of scientific approaches to a holistic system of ideas and beliefs in the disclosure of the scientific content of the phenomenon of "school"; the pedagogical aspect of the Ukrainian Piano School; the structure and its functional components; the awareness of the self-sufficiency of the Ukrainian musical-pedagogical tradition, its integration into the modern world educational space; the disclosure of the context of the scientific content of the Ukrainian Piano School. The practical concept deepens the understanding of the historical achievements of the leading educators in the process of studying their genealogical trees on the basis of awareness of the tradition as a leading factor in the modern development of the Ukrainian piano school. It is possible to widely apply the generalized pedagogical experience of the Ukrainian Piano School in modern practice of training specialists for the process of personal activities.